2013
DOI: 10.1245/s10434-012-2836-y
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Preoperative Imaging in Small Bowel Neuroendocrine Tumors

Abstract: CT and SRS are complementary in making the diagnosis of SBNET, with CT giving more precise anatomical detail, while SRS helps to confirm that lesions are NETs and is useful for identifying occult extrahepatic sites of metastatic disease. However, 10-15 % of SBNETs were not identified by either test preoperatively, and therefore surgical exploration still plays an important role in making the diagnosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The imaging assessment should specify the primary sites (30% multiple) often small in size, the lymph node stage and the presence of hepatic nodules [2,3] . Both CT and MR showed a similar rate of sensitivity in staging disease preoperatively but CT seems to be more effective in detecting anatomical details that matter from a surgical standpoint (i.e., vascular invasion, lymph node involvement) [4,5] . MR, either in T2 sequences or with diffusion-weighted sequences, could better detect hepatic nodules [6] .…”
Section: What Should Be the Minimal Enets Standard Of Care For Preopementioning
confidence: 97%
See 1 more Smart Citation
“…The imaging assessment should specify the primary sites (30% multiple) often small in size, the lymph node stage and the presence of hepatic nodules [2,3] . Both CT and MR showed a similar rate of sensitivity in staging disease preoperatively but CT seems to be more effective in detecting anatomical details that matter from a surgical standpoint (i.e., vascular invasion, lymph node involvement) [4,5] . MR, either in T2 sequences or with diffusion-weighted sequences, could better detect hepatic nodules [6] .…”
Section: What Should Be the Minimal Enets Standard Of Care For Preopementioning
confidence: 97%
“…Since the reported correlation between siNETs and other colorectal neoplasms, a colonoscopy may be included in the preoperative workup [8] . A meticulous intraoperative exploration of all abdominal cavity and the palpation of the whole jejunum and ileum are superior to all imaging modalities and should be systematically executed [4,5] .…”
Section: What Should Be the Minimal Enets Standard Of Care For Preopementioning
confidence: 99%
“…For CT diagnosis of a pancreatic NET (pNET), the lesion detection rates range from 69 to 94% [7][8][9] and 67% sensitivity was reported in one study [10] and 96% in another including patients with von Hippel-Lindau disease [11] . CT sensitivity for NET liver metastases ranges from 75 to 100% [3,[12][13][14][15] and specificity from 83 to 100% [10,12,14,15] .…”
Section: Sensitivity Specificity and Detection Ratementioning
confidence: 99%
“…For lymph node metastases, CT shows 60-70% sensitivity and 87-100% specificity [13,15,17] . For other soft tissue metastases, a 62-67% sensitivity and 98-100% specificity has been reported for CT [3,12,14] .…”
Section: Sensitivity Specificity and Detection Ratementioning
confidence: 99%
“…One recent study evaluating OctreoScans in patients with surgically confirmed small bowel NETs found that either the primary tumor or adjacent nodes had uptake in 74 % of cases, and liver metastases in 66 % (of cases where metastases were present). 4 Functional imaging for NETs has used other agents over the years, including 123 I-Tyr 3 -octreotide and 123 I-MIBG, in addition to the standard of 111 In-octreotide. A more contemporary improvement has come from combining functional imaging with positron emission tomography (PET).…”
mentioning
confidence: 99%